2013
DOI: 10.4103/0972-0707.120937
|View full text |Cite
|
Sign up to set email alerts
|

Role of mineral trioxide aggregate in management of external root resorption

Abstract: External root resorption (ERR) is a lytic process occurring in the cementum or cementum and dentin of the roots of teeth. Here we report a case of inflammatory ERR in a mandibular right molar in a 22-year-old male patient with history of incomplete root canal treatment with the same. Considering the biological properties of mineral trioxide aggregate cement, especially its alkalinity and sustained calcium hydroxide release, this material was used for the treatment of ERR, followed by permanent prosthesis. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…MTA was chosen as the root canal filling material because of its reported properties such as biocompatibility, antimicrobial activity, hydrophilicity, and excellent sealing ability. Consistent with this case report, previous studies have reported the successful use of MTA in teeth with necrotic pulps and open apices associated with external root resorption 19 …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…MTA was chosen as the root canal filling material because of its reported properties such as biocompatibility, antimicrobial activity, hydrophilicity, and excellent sealing ability. Consistent with this case report, previous studies have reported the successful use of MTA in teeth with necrotic pulps and open apices associated with external root resorption 19 …”
Section: Discussionsupporting
confidence: 91%
“…Consistent with this case report, previous studies have reported the successful use of MTA in teeth with necrotic pulps and open apices associated with external root resorption. 19 A surgical intervention was subsequently done with an objective of complete debridement of the osseous defect, root end resection, and reshaping to reposition the root within the alveolar housing. 7,12 The ultimate goal of periodontal therapy is to prevent further loss of attachment and restore the supporting periodontal tissues lost due to disease or trauma.…”
Section: Case Reportmentioning
confidence: 99%
“…[2122] The high pH increases the permeability of cell membranes with leakage of intracellular components. [13] Therefore, MTA and calcium hydroxide seem to possess similar antimicrobial action.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the antifungal action of MTA, it has been shown that the mechanism of action of MTA involves the dissolution of calcium oxide, which increases pH by releasing Ca +2 and OH − . [ 21 22 ] The high pH increases the permeability of cell membranes with leakage of intracellular components. [ 13 ] Therefore, MTA and calcium hydroxide seem to possess similar antimicrobial action.…”
Section: Discussionmentioning
confidence: 99%
“…One of the major challenges in endodontic treatment of teeth with open apices due to resorption is achieving effective debridement, canal disinfection and subsequent sealing of the root canal space. The key point is to form an apical barrier or a stop against which one can place the sealer and gutta-percha, while avoiding over-extrusion 17,21 .Mineral trioxide aggregate (MTA) is a reliable material due to its biocompatibility and good sealing properties,which providesopportunities for the regeneration of periapical tissues,such as periodontal ligament, bone and cementum 1,2,15 .…”
Section: Introductionmentioning
confidence: 99%